COMPARATIVE ANALYSIS OF THE RATE OF VITAMIN C DEGRADATION IN LETTUCE (LACTUCA SATIVA) TREATED WITH VARIOUS PRETREATMENT SOLUTIONS (FUDMA JOURNAL OF SCIENCES, 2025)
Lettuce is a highly perishable leafy vegetable that faces significant postharvest challenges, including water loss, browning, microbial contamination, and ethylene sensitivity. These issues lead to reduced shelf life, economic losses, and food waste, affecting both farmers and consumers. This study aimed to establish a kinetic model for the breakdown of ascorbic acid in lettuce via computer simulations. The vegetable samples were examined using high-performance liquid chromatography (HPLC) to assess the ascorbic acid (AA) content of the vegetables after they were dipped at various time intervals. This consists of an isocratic elution procedure with ultraviolet-visible detection at 245 nm. The average coefficient of determination (R2-value), was greater than 0.9088, indicating that the AA degradation in the experiment followed a first-order kinetic model. Using the integrated law approach, rate constants of 0.0135, 0.0460, and 0.0341 k (min-1) and half-lives of 51.3442, 15.0684, and 20.3269 minutes for lettuce dipped in NaCl, SB, and SM, respectively were determined. The Arrhenius equation was used to calculate the activation energies of 161.5341, 84.2009, and 48.6334 kcal/mol. Time series analysis was used to predict the amount of vitamin C at point "70" (Y-INTERCEPT), which was 2.3167, 0.1438, and 0.9561 mg/100 g. In(C): 6.800551, 6.570627, and 6.630127 were obtained when the kinetic models were constructed using the expected initial concentration, processing time, and observed contents respectively. This suggests that In(C) is directly influenced by the initial vitamin C concentration, with an In(Co) concentration of 898.41 mg/100 g, a rate constant, and time. The best result was obtained by...
Keywords: Vitamin C; Degradation; kinetics; Lettuce; Pretreatment